Enhancing Writing Report Texts Using Padlet Website: The Perceptions - Sukma Nur Ardini; Marlinda Marlinda (Journal of Languages and Language Teaching, 2023)
There are several technology-based solutions available to help students with disabilities related to compose something. However, merely providing access to technology is insufficient. It is important to utilized technology because the impelentation of using technology have an impact on students’ outcomes. The aim of this study is to investigate the perceptions in utilizing Padlet as a learning medium in writing report texts. Descriptive qualitative method was employed using questionnaire and interview. They were distributed through 36 sample of grade X and one teacher. 78% of the participants had positive perceptions; 19% neutral and 3% negative. It assumed that most of the students found that using Padlet website provided a more engaging and interactive writing experience. It was also revealed that the students who gave feedback negative and neutral perceptions had another argument that there are more learning media instead of Padlet which can increase his writing skill. The teacher supported the findings and provide nine description on how she perceived Padlet as learning media. Overall, using Padlet as a collaborative writing approach has the potential to connect and develop students' writing skills. This study is useful for writing teachers since the benefits of Padlet can make the writing process more effective and engaging, which relates to 21st Century Teaching and Learning.